Lidar Observed Optical Properties of Tropical Cirrus Clouds Over Gadanki Region - Manoj Kumar, Nellore; Venkatramanan, Kannan (Frontiers in Earth Science, 2020)
The presence of cirrus cloud has its impact on the earth’s radiation budget. In order to study the effect of cirrus clouds in the tropical regions, it is essential to understand and characterize their optical properties. The optical properties of high altitude cirrus clouds are obtained using the polarization diversity ground based Mie lidar instrument at a tropical latitude station in the Indian subcontinent. Lidar measurements are taken for one year (2013) at National Atmospheric Research Laboratory (NARL), located at Gadanki (13.5° North, 79.2° East; 375m AMSL), India and are used for the present investigation. Altitude variations of optical depth and depolarization ratio are discussed. In the altitude range of 10–17 km, the range of the optical depth and depolarization ratio of cirrus cloud was found to be 0.01–0.4 and 0.1–0.4 respectively. The interdependence of optical depth as a function of depolarization ratio is analyzed and a positive correlation is observed (0.3950). From the measured optical depth values, it is categorized that 8%, 77% and 14% of the cirrus clouds are sub-visual, thin and thick clouds. The monthly and seasonal variations of optical properties of cirrus clouds were analyzed. Summary of cirrus cloud layer statistics and the statistical variation (seasonal) of the optical properties of cirrus clouds is presented for the period of study.